(untitled) (Research, Society and Development, 2020)
The health aspects associated with fermented milk products have resulted in increased consumption of this beverage. Three fermented beverages added with cashew pulp and different concentrations of whey (10, 20 and 30 %) were produced, being stored for a period of 28 days and evaluated regarding their physicochemical, microbiological and sensory characteristics. Fifty-two tasters evaluated acceptance of the beverages using hybrid 9-point hedonic scales. It was found that the lower the proportion of whey used in the beverages, the higher the total solids, proteins, fat and caloric values (p<0.05). Regarding ash values, no significant differences were observed (p>0.05). Beverages pH values did not differ when evaluated on the same day of storage (p>0.05). After 7, 14, 21 and 28 days of storage, differences were observed (p <0.05) regarding acidity values, except for the time 0. The beverages presented probiotic viability during the storage period, being the count above the minimum recommended by the current Brazilian legislation. Even though the beverages added with 10 % of whey presented a better acceptability index, the other beverages developed in this study presented good acceptance by the tasters. The probiotic beverages flavored with cashew fruit were nutritionally and technologically viable and presented physicochemical and microbiological stability during refrigerated storage for 28 days.